Pengaruh Konsentrasi POC Urine Kelinci dan Dosis Pupuk NPK Mutiara Terhadap Pertumbuhan dan Produksi Tanaman Terong Ungu (Solanum Melongena L.) - Muhammad Wilda Mahbubi; NANIK FUROIDAH (Program Studi Agroteknologi, 2026)
This study aims to determine the effect of giving POC Rabbit Urine and Pearl NPK on the growth and production of purple eggplant (Solanum melongena L.). This research was carried out in Dukuh Hamlet, Dukuhdempok Village, Wuluhan District, Jember Regency with an altitude of 12.43 meters above sea level, starting in November 2024 until January 2025. This study was conducted using a 4x3 Factorial Group Random Design with 3 replicates consisting of 2 treatment factors, namely 1) Rabbit Urine POC (U) consisted of 4 levels, namely: U0 = control, U1 = 85 ml/L plant, U2 = 95 ml/L plant, and U3 = 105 ml/L plant, and 2) NPK Pearl (M) consisted of 3 levels, namely: M0 = control, M1 = 15 g/plant, M2 = 20 g/plant, and M3 = 25 g/plant. The observed parameters of plant height, number of leaves, number of branches, flowering age, harvest age, number of crops, weight for association, weight of plant fruit. The data obtained is analyzed with an analyses of variance (ANOVA), if it is significantly different, it is followed by a Duncan test with a level of 5% using Microsoft Excel. The results showed that the concentration of Rabbit POC Urine 95 ml/L per plant (U2) had the best influence on the parameters of the number of branches, unity fruits, and the concentration of POC Rabbit Urine 105 ml/L (U3) of the crop had the best influence on the weight of the plant. Meanwhile, the dose of NPK Mutiara fertilizer 25 g/plant (M3) has the best influence on the height of the plant, the number of branches, the number of plant fruits, the weight of the plant's fruits, and the dose of NPK Mutiara fertilizer of 20 g/plant (M2) has the best influence on the number of leaves. The interaction between Rabbit POC Urine and Pearl NPK had no noticeable effect on all observation parameters.